2011
DOI: 10.1021/ac200447b
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phosphatase- and Redox Cycling-Based Immunosensors and Its Application to Ultrasensitive Detection of Troponin I

Abstract: The authors herein report optimized conditions for ultrasensitive phosphatase-based immunosensors (using redox cycling by a reducing agent) that can be simply prepared and readily applied to microfabricated electrodes. The optimized conditions were applied to the ultrasensitive detection of cardiac troponin I in human serum. The preparation of an immunosensing layer was based on passive adsorption of avidin (in carbonate buffer (pH 9.6)) onto indium-tin oxide (ITO) electrodes. The immunosensing layer allows ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
114
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 29 publications
2
114
0
Order By: Relevance
“…It can remove a phosphate group from the substrate by hydrolyzing phosphoric acid monoesters into a phosphate ion and an electroactive molecule with a free hydroxyl group. Recently, the strategy for signal amplification using an ALP-based enzymatic reaction plus a redox-cycling reaction has been particularly popular in electrochemical immunoassays since it only requires the addition of more chemicals to the electrolyte solution and not a change in the detection procedure of conventional enzyme-based immunoassays [16][17][18][19][20][21][22][23][24]. In the system, the enzymatic product is regenerated after its electrochemical oxidization by a chemical reducing reagent, thus amplifying the electrochemical signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can remove a phosphate group from the substrate by hydrolyzing phosphoric acid monoesters into a phosphate ion and an electroactive molecule with a free hydroxyl group. Recently, the strategy for signal amplification using an ALP-based enzymatic reaction plus a redox-cycling reaction has been particularly popular in electrochemical immunoassays since it only requires the addition of more chemicals to the electrolyte solution and not a change in the detection procedure of conventional enzyme-based immunoassays [16][17][18][19][20][21][22][23][24]. In the system, the enzymatic product is regenerated after its electrochemical oxidization by a chemical reducing reagent, thus amplifying the electrochemical signal.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reducing reagent can also prevent the auto-oxidation of the enzymatic product. Among the commonly used ALP substrate/product couples, including 4-aminophenyl phosphate (p-APP)/4-aminophenol (p-AP), hydroquinone diphosphate (HQDP)/hydroquinone (HQ), L-ascorbic acid 2-phosphate (AAP)/L-ascorbic acid (AA), 4-amino-1-naphthyl phosphate (ANP)/4-amino-1-naphthol (AN) and 1-naphthyl phosphate (NPP)/1-naphthol (NP), AAP is better because of its low cost, the easy dissolution of AAP and AA in aqueous solutions, the high formal potential of AAP and low formal potential of AA and the high signal-to-background ratio [20]. Self-assembled monolayer (SAM) on gold has been used frequently for controlling the adsorption of biomolecules and developing electrochemical biosensors [1,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hydrolysis of 4-aminopheyl-␤-d-galactopyranoside (APGP) by Gal generates an electroactive 4-aminophenol (AP) [21][22][23][24]. Some of the recent studies have shown that electrochemical-chemical (EC) redox cycling [25,26] and electrochemical-chemical-chemical (ECC) redox cycling [27][28][29][30] of the enzyme product allows for high signal amplification, thereby lowering the detection limits. The electrochemical redox cycling schemes can be combined with the enzymatic reaction simply by adding one or two chemical species to the solution without using an additional electrode or enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac troponin I (cTnI), a part of the troponin complex present in cardiac muscle tissues, is a reliable biomarker of cardiac muscle tissue injury and is widely used in the early diagnosis of acute myocardial infarctions [1,2]. Although an increase in cTnI concentration from 10 pg mL −1 to over 1 ng mL −1 into blood vessels within a few hours occurs during the damage to cardiac muscles, it is present at ultralow levels following the onset of acute myocardial infarction symptoms.…”
Section: Introductionmentioning
confidence: 99%